2019
DOI: 10.5851/kosfa.2018.e58
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a Bile-responsive Expression System in Lactobacillus plantarum

Abstract: This study aimed to develop a bile-responsive expression system for lactobacilli. The promoters of four genes, encoding phosphoenolpyruvate-dependent sugar phosphotransferase (mannose-specific), L-lactate dehydrogenase (LDH), HPr kinase, and D-alanine-D-alanine ligase, respectively, which were highly expressed by bile addition in Lactobacillus johnsonii PF01, were chosen. Each promoter was amplified by polymerase chain reaction and fused upstream of the β-glucuronidase gene as a reporter, respectively. Then, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…It was combined with pUC19 by cloning into the Sac I site; the erythromycin resistance gene (GCA_000219475.3) from L. johnsonii PF01, as a selection marker, was cloned into the Kpn I site. The bile inducible promoter of the lactate dehydrogenase 1 gene (GCA_000219475.3) [ 18 ] from L. johnsonii PF01 was PCR-amplified and Sal I and Pst I sites were cloned to express the target gene. The signal peptide and cell wall anchor of the surface layer protein A (SlpA) gene (Uniprot ID P35829) from L. acidophilus ATCC 4356 were amplified using PCR and located downstream of the target gene for cell wall anchoring of the target protein.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was combined with pUC19 by cloning into the Sac I site; the erythromycin resistance gene (GCA_000219475.3) from L. johnsonii PF01, as a selection marker, was cloned into the Kpn I site. The bile inducible promoter of the lactate dehydrogenase 1 gene (GCA_000219475.3) [ 18 ] from L. johnsonii PF01 was PCR-amplified and Sal I and Pst I sites were cloned to express the target gene. The signal peptide and cell wall anchor of the surface layer protein A (SlpA) gene (Uniprot ID P35829) from L. acidophilus ATCC 4356 were amplified using PCR and located downstream of the target gene for cell wall anchoring of the target protein.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous studies have demonstrated the potential of L. plantarum SK156 as an effective host for expressing bioactive substances in the intestine owing to its bile-responsive expression system [ 18 , 19 ]. In this study, the possible antigenic determinants of the spike, membrane, and envelope proteins of SARS-CoV-2 were predicted and displayed on the surface of recombinant L. plantarum strains.…”
Section: Introductionmentioning
confidence: 99%
“…A bile-responsive E. coli-Lactobacillus shuttle expression vector, pULP3-P LDH , for Lactobacillus spp. was generated by fusing pUC19 with the L. plantarum plasmid pLP27, which has been found to persist in L. plantarum for up to 80 generations without selection pressure [90].…”
Section: Vectors Properties Reference Pnz9573mentioning
confidence: 99%
“…A careful design must be taken into consideration, where the selection markers for constructing vectors should not rely on antibiotic resistance selection for successful cloning, but on other selective marker genes, such as auxotrophic mutant complementation or use of the CRISPR/Cas system [ 105 ]. Once achieved, lactobacilli show promising potential not only in health promotion, immunomodulation, and tolerance [ 104 , 106 ], but also in its observed genetic stability after genetic manipulation [ 107 ].…”
Section: Bacterial Mucosal Vaccines In the Literaturementioning
confidence: 99%